2005
DOI: 10.1099/vir.0.80927-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and characterization of novel coronaviruses infecting graylag geese (Anser anser), feral pigeons (Columbia livia) and mallards (Anas platyrhynchos)

Abstract: In light of the finding of a previously unknown coronavirus as the aetiology of the severe acute respiratory syndrome (SARS), it is probable that other coronaviruses, than those recognized to date, are circulating in animal populations. Here, the results of a screening for coronavirus are presented, using a universal coronavirus RT-PCR, of the bird species graylag goose (Anser anser), feral pigeon (Columbia livia) and mallard (Anas platyrhynchos). Coronaviruses were found in cloacal swab samples from all the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
137
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(147 citation statements)
references
References 53 publications
4
137
0
6
Order By: Relevance
“…Point mutations or deletions in the S protein and NSPs have been associated with changes in tropism and virulence of coronaviruses ( 4 7 , 13 ). CCoV strain CB/05 showed intact structural and nonstructural proteins, with an S protein closely related to that of other type II CCoVs.…”
Section: Discussionmentioning
confidence: 99%
“…Point mutations or deletions in the S protein and NSPs have been associated with changes in tropism and virulence of coronaviruses ( 4 7 , 13 ). CCoV strain CB/05 showed intact structural and nonstructural proteins, with an S protein closely related to that of other type II CCoVs.…”
Section: Discussionmentioning
confidence: 99%
“…M41). 4b: Jonassen et al (2005) have shown that the region of the greylag goose coronavirus genome downstream of the N gene is much larger than that of IBV, TCoV and PhCoV. Moreover, the additional sequence contains two TASs.…”
Section: Detection Of Coronaviruses In Birdsmentioning
confidence: 99%
“…UTRs of the coronaviruses detected in greylag goose, mallard duck and pigeons are very similar to those of IBV, TCoV and PhCoV, confirming the highly conserved nature of this region of the 3? UTR (Jonassen et al ., 2005). Comparison of the sequences of primers UTR11…”
Section: Detection Of Coronaviruses In Birdsmentioning
confidence: 99%
“…Either point mutations or deletions in the structural spike glycoprotein and in the nonstructural proteins have been associated to changes in tropism and virulence of coronaviruses [72,78,83,93,160]. The porcine respiratory coronavirus (PRCoV), a spike (S) gene deletion mutant of transmissible gastroenteritis virus (TGEV), causes mild or subclinical respiratory infections in pigs [93].…”
Section: Pantropic Canine Coronavirusmentioning
confidence: 99%